Design and validation of the stress coping scale in parents of children with disabilities - Tanta-Luyo, Araseli Yaquelin (2020)
The objective of this article was to determine the psychometric evidence of the coping scale in parents of children with disabilities in Lima. The study was a non-experimental, cross-sectional and psychometric design. The sampling was not probabilistic and at the convenience of the researchers with a sample of 246 parents from three special basic education centers, in an age range of 20 to 57 years. The validation development was developed with the validity based on the content through expert judgment and psychometric evaluation in two studies. The results presented appropriate empirical evidence of validity by internal structure, based on “the one-dimensional model - Focused on the problem of 10 items (SB-X2 / gl = 1.79, CFI = .92, SRMR = .06, RMSEA = .06) ” and an internal consistency, using omega compound ω = .79. In conclusion, the coping scale for parents of children with disabilities evidenced adequate psychometric properties, confirming the dimension centered on the problem of the theory of Lazarus and Folkman (1986).